Coronavirus Disease Outbreak in Call Center, South Korea - Park, Shin Young; Kim, Young-Man; Yi, Seonju; Lee, Sangeun; Kim, Chang Bo; Kim, Jung-il; Kim, Hea Sook; Kim, Young Bok; Park, Yoojin; Huh, In Sil; Kim, Hye Kyung; Yoon, Hyung Jun; et al. (Emerging infectious diseases, 2020)
We describe the epidemiology of a coronavirus disease (COVID-19) outbreak in a call center in South Korea. We obtained information on demographic characteristics by using standardized epidemiologic investigation forms. We performed descriptive analyses and reported the results as frequencies and proportions for categoric variables. Of 1,143 persons who were tested for COVID-19, a total of 97 (8.5%, 95% CI 7.0%-10.3%) had confirmed cases. Of these, 94 were working in an 11th-floor call center with 216 employees, translating to an attack rate of 43.5% (95% CI 36.9%-50.4%). The household secondary attack rate among symptomatic case-patients was 16.2% (95% CI 11.6%- 22.0%). Of the 97 persons with confirmed COVID-19, only 4 (1.9%) remained asymptomatic within 14 days of quarantine, and none of their household contacts acquired secondary infections. Extensive contact tracing, testing all contacts, and early quarantine blocked further transmission and might be effective for containing rapid outbreaks in crowded work settings.